Weekly Reader Books presents Ramona forever - Cleary, Beverly; Tiegreen, Alan (New York : Morrow, 1984)
Ramona's year in third grade is highlighted by the arrival of Howie's rich uncle, a change in her after-school situation, a surprise wedding, a death and a new arrival in the family, and her father's getting a job.
Keywords: Families -- Fiction